2020
DOI: 10.2166/wcc.2020.259
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atmospheric rivers on cold-season heavy precipitation events in Iran

Abstract: Atmospheric rivers (ARs) as massive and concentrated water vapour paths can have a critical impact on extreme events in arid and semi-arid areas. This study investigated the effect of ARs on heavy precipitation events during the cold, rainy months (November–April) in Iran for 11 years. The results showed that 107 ARs had an influence on heavy precipitation, which providing partial moisture for Iran's precipitation. On average, 11 heavy precipitation days were linked to the presence of ARs in the six cold month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The agreement rate mentioned above for other regions gives us confidence that the results we investigate in our current study would not heavily change if another detection algorithm was to be developed or used. In that regard, it is noted that the Iran-focused study in Esfandiari and Lashkari (2020ab) [49,50] used AR IVT percentile and geometry criteria largely following our global algorithm used here. We direct readers to Guan and Waliser (2015) for more information on the AR detection algorithm used in our study.…”
Section: Ar Detection Algorithmmentioning
confidence: 99%
“…The agreement rate mentioned above for other regions gives us confidence that the results we investigate in our current study would not heavily change if another detection algorithm was to be developed or used. In that regard, it is noted that the Iran-focused study in Esfandiari and Lashkari (2020ab) [49,50] used AR IVT percentile and geometry criteria largely following our global algorithm used here. We direct readers to Guan and Waliser (2015) for more information on the AR detection algorithm used in our study.…”
Section: Ar Detection Algorithmmentioning
confidence: 99%
“…ARs frequently produce heavy, impactful precipitation over where they are forced upward by orography (Ralph et al, 2004). While ARs and their impacts, which range from very beneficial to very detrimental, have traditionally been studied as a western U.S. phenomenon (Dettinger, 2011, 2013; Guan et al, 2010; Neiman et al, 2013; Ralph, Rutz, et al, 2019), it has become apparent that ARs affect many low‐, middle‐, and high‐latitude regions of the world (Dezfuli, 2020; Gorodetskaya et al, 2014; Ramos et al, 2015; Thapa et al, 2018; Viale et al, 2018; Wille et al, 2019; Yang et al, 2018; and Esfandiari & Lashkari, 2020; to name a few).…”
Section: Introductionmentioning
confidence: 99%
“…They employed speci c humidity (q) to identify ARs and tracking. In the same study Esfandiari and Lashkari (2021), show that on average, 11 heavy precipitation days were linked to the presence of ARs in the six cold months of each year in Iran that December experienced the highest frequency of ARs linked to heavy precipitation during the statistical period. They showed that more than half of the ARs originated from the Gulf of Aden and the Red Sea.…”
Section: Introductionmentioning
confidence: 77%
“…Especially in semi-arid and arid regions, local water vapor cannot cause heavy rainfall, thus moisture transported into this regions (Barati and Heydari, 2003;Heydarizad et al, 2018;MOHAMMADI and MASOUDIAN, 2010). Recent studies use Atmospheric river (AR) term to refer to moisture transport over Iran (Akbary et al, 2019;Esfandiari and Lashkari, 2021).…”
Section: Introductionmentioning
confidence: 99%